Can Exchange Rates Be Predicted? - Siriwutiset, Trin (2007)
Foreign exchange rates produce significant impacts on both the macroeconomic and microeconomic scale. CountriesÃ¢ÂÂ government and multinational companies have been seeking ways to stabilize the exchange rates for a few decades. However, there is no perfect consensus on methods to control and stabilize the exchange rates. In fact, there are several occasions in history where turbulence movements caused crisis in the economies.